2020
DOI: 10.1016/j.jpsychires.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of trajectories of depressive symptoms with vascular risk, cognitive function and adverse brain outcomes: The Whitehall II MRI sub-study

Abstract: Background: Trajectories of depressive symptoms over the lifespan vary between people, but it is unclear whether these differences exhibit distinct characteristics in brain structure and function. Methods: In order to compare indices of white matter microstructure and cognitive characteristics of groups with different trajectories of depressive symptoms, we examined 774 participants of the Whitehall II Imaging Sub-study, who had completed the depressive subscale of the General Health Questionnaire up to nine t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(46 reference statements)
1
14
1
Order By: Relevance
“…Recent longitudinal data showed that only individuals with depressive symptoms that increased in late-life, and no other trajectories of depressive symptoms across the life course, had higher white matter hyperintensity volumes (71). In addition, only this trajectory has been associated with greater decline in executive function (71), and higher risk of dementia (72,73).…”
Section: Contribution Of Microvascular Dysfunction To Apathy Cognitive Dysfunction and Stroke In Depressionmentioning
confidence: 99%
“…Recent longitudinal data showed that only individuals with depressive symptoms that increased in late-life, and no other trajectories of depressive symptoms across the life course, had higher white matter hyperintensity volumes (71). In addition, only this trajectory has been associated with greater decline in executive function (71), and higher risk of dementia (72,73).…”
Section: Contribution Of Microvascular Dysfunction To Apathy Cognitive Dysfunction and Stroke In Depressionmentioning
confidence: 99%
“…However, whether brain differences reflect vulnerability or long-term ‘scarring’ consequences cannot be concluded from our cross-sectional study. Longitudinal studies have suggested that differences might be related to depression onset or vulnerability rather than be the result of depressive episodes ( Binnewies et al, 2021 , Demnitz et al, 2020 ), although findings are inconsistent ( Dohm et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptom was assessed using the Center for Epidemiologic Studies Depression Scale-8 (CES-D 8) for HRS participants, and participants scoring 4/8 or above were defined as having depressive symptom[35]. In the FOS and WII, a 20-item CES-D was used, and a score of 16/60 or above indicated depressive symptom[36,37]. In the FOS and WII where physical and blood examination was regularly administered, we additionally identified participants with hypertension [38](with anti-hypertensive medication or systolic blood pressure >=130 mmHg or diastolic blood pressure>=80 mmHg), diabetes [39](with oral hypoglycemic medication or insulin use, fasting blood glucose concentrations ≥126 mg/dL, or non-fasting blood glucose concentrations ≥200 mg/dL), and hypercholesterolemia [40](with cholesterol-lowering medication or total cholesterol concentrations ≥200 mg/dL, i.e., 5.20 mmol/L).…”
Section: Methodsmentioning
confidence: 99%